Investigation of kinetics conformities with a law of decomposition of agglomerates of microorganisms in the condition of acoustic cavitation - Старчевский, Владимир Людвигович; Кисленко, Владимир Николаевич; Максымив, Наталья Любомировна; Олийнык, Лилианна Петровна (Eastern-European Journal of Enterprise Technologies, 2014)
Our results show that the amount of agglomerates of microorganisms decreases during the sonication and the concentration of individual microorganisms in suspension increases proportionally to the sonication time, the radius of colonies of cellular microorganisms decreases. Concentration of microorganism colonies increases linearly with time. This allows to calculate the rate of colonies decomposition into smaller. The total surface of the particles, participating in the aggregate formation is proportional to the aggregate concentration in the system and the surface, involved in the bonds between the particles in a single aggregate. Cavitation energy is spent on the destruction of bonds between particles in the aggregate, which is obviously proportional to the surface of surface segments of individual cells, connecting them with the neighbors in the colony. The reaction order on the aggregate concentration in the system is different from the first one. We have proposed an equation, which describes the destruction process of cell colonies of microorganisms under the influence of ultrasound.